Effect of Speed and Turning Time Pulley on the Quantity and Quality of Output Multipurpose Chopper Machine - Sari, Kartika; Sunardi, Sunardi; muwaffaq, Abiyyu Sayyid; Aminuddin, Jamrud; Khoryanton, Ampala; Warso, Warso; Budi Utomo, Agung Bambang (Politeknik Negeri Lhokseumawe, 2023)
Variation of pulley rotational speed on the yield and cut of the multipurpose chopper aims to determine the optimum quality and quantity of chopping results. Testing using cassava and bananas. The diameter of the pulley used is 2 inches and the driven pulley is 6, 7, and 10 inches with a pulley speed of 467, 400, and 275 rpm. The result of bananas shows that the average chopping was 573, 864, and 864 grams, respectively with the spin pulley time being 46, 90, and 59 seconds. Meanwhile, for cassava, the results of chopping were 984, 995, and 823 grams, respectively with the spin pulley time being 23, 59, and 35 seconds, respectively. The optimum chopping quality for bananas used a pulley diameter of 10 inches and an optimum rotation time was 59 seconds. The optimum slicing quality for cassava uses a pulley diameter of 7 inches with an optimum rotation time was 59 seconds. The conclusion is that the diameter of the pulley affects the thickness of the sample, the time and speed of the pulley rotation, and the quality of the chopping results.